2011
DOI: 10.1007/s11745-011-3643-0
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Supplementation Improves Neutrophil Function During Cancer Chemotherapy

Abstract: Cancer chemotherapy is associated with neutropenia and impaired neutrophil function. This study aimed to investigate whether supplementation with low dose fish oil (FO), providing n-3 polyunsaturated fatty acids, in cancer patients receiving chemotherapy after surgical tumor (mainly gastrointestinal) removal is able to improve the function of blood neutrophils. Patients (n = 38) receiving chemotherapy (5-fluorouracil and leucovorin) were randomized into two groups; one group (control) did not receive a supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 39 publications
6
39
0
8
Order By: Relevance
“…Plasma levels of reactive oxygen species were also significantly lower in the fish oil group compared with the placebo group at two experimental timepoints [25]. Similarly, the fish oil group of the Bonatto et al study (2012) exhibited significantly higher levels of superoxide production by polymorphonuclear cells (average, 28%), and significantly lower levels of hydrogen peroxide production, compared to the control group [20]. To summarize, modification in level and quantity of oxidative products by EPA and DHA fish oil observed in these studies could be crucial to explain their cytotoxicity toward cancer cells and their ability to inhibit cancer cell growth.…”
Section: Oxidative Statusmentioning
confidence: 85%
See 3 more Smart Citations
“…Plasma levels of reactive oxygen species were also significantly lower in the fish oil group compared with the placebo group at two experimental timepoints [25]. Similarly, the fish oil group of the Bonatto et al study (2012) exhibited significantly higher levels of superoxide production by polymorphonuclear cells (average, 28%), and significantly lower levels of hydrogen peroxide production, compared to the control group [20]. To summarize, modification in level and quantity of oxidative products by EPA and DHA fish oil observed in these studies could be crucial to explain their cytotoxicity toward cancer cells and their ability to inhibit cancer cell growth.…”
Section: Oxidative Statusmentioning
confidence: 85%
“…In the Bonatto et al study (2012), the fatty acid composition of PMNC was found to be altered in the fish oil group, with significant increases in levels of EPA and DHA, and a significant decrease in levels of arachidonic acid (AA), observed. In contrast, the fatty acid composition of the control group remained unchanged [20]. In the Mocellin et al (2013) study, plasma levels of EPA and DHA increased significantly by an average of 1.8-fold and 1.4-fold, respectively (at baseline vs. week 9: p < 0.05) [23].…”
Section: Incorporation Of Epa and Dhamentioning
confidence: 89%
See 2 more Smart Citations
“…Animal and human studies showed incorporation of n-3 FA to be associated with a reduction of proinflammatory cytokines and PGE2, after supplementation of at least 2 g of EPA per day in healthy subjects [16,17], patients with cancer [18][19][20], sepsis [21] and ARDS [22][23][24]. Supplementation of a lower dose of EPA did not modulate immune function in humans [25][26][27]. Small clinical studies from a Japanese group showed the relationship of GVHD and inflammation, and the probable beneficial effects of EPA [6,7].…”
Section: Discussionmentioning
confidence: 97%